Time-resolved Spectroscopy of Charge Transfer at the Interface of Nanomaterials and Porphyrins - ARPAÇAY, PINAR (Trinity College Dublin. School of Physics. Discipline of Physics, 2018)
In order to optimize performance in many light-harvesting systems such as photovoltaics and photocatalysis, a fundamental comprehension of interfacial electron transfer at the interfaces of donor (D)-acceptor (A) systems is quite important. The relevant parameters that are involved in charge transfer, charge separation, charge recombination, intersystem crossing, triplet state lifetime at porphyrin-based donor-acceptor interfaces are the main focuses in the discussions in this thesis. To investigate the charge transfer processes in various donor-acceptor systems, a combination of steady-state, time-resolved transient absorption (TA) and photoluminescence spectroscopies were used. Furthermore, photophysical properties (absorption spectra, fluorescence spectra, singlet and triplet state lifetimes) of newly synthesized 5,10-disubstituted push-pull porphyrins (Am1 5,10-1 and SlpE029) and their 5,15-disubstituted isomers (Am1 5,15-1 and SlpE026) were studied in this thesis. While ground-state and excited-state properties are very similar for the Am1 5,10-1 and Am1 5,15-1 porphyrins, slight differences exist among the isomers of the SlpE029 and SlpE026. Clear correlations were also observed between the steady-state measurements and time-resolved spectroscopy results which can be explained by greater extent of intramolecular charge transfer between the D and A groups and this case was most observed in the SlpE029 porphyrin. Although the singlet state lifetime of all of the investigated porphyrins was almost the same, interestingly the longest triplet state lifetime was recorded in SlpE026 porphyrin, followed by SlpE029, and then Am1 5,15-1 and Am1 5,10-1 with the almost same triplet state lifetime. Additionally, the process of photoinduced electron transfer was investigated for the first time between methylammonium lead triiodide perovskite film and the porphyrin interface with a case study using the SlpE026 porphyrin. Additionally, the interfacial charge transfer dynamics between two neutral porphyrins (Am1 5,15-1 and SlpE026) with different polymorph of nanocarbon (neutral fullerene, C60 and negatively charged graphene carboxylate, GC) were investigated using steady-state measurements and nanosecond (ns) and femtosecond (fs) TA spectroscopies. Static and a combination of static and dynamic quenching in the presence of GC and C60, were studied through fs and ns-TA as well as being demonstrated by Stern-Volmer plots. Moreover, fs-TA spectroscopy revealed that both porphyrins presented strong ground state bleach corresponding to the depletion of the Soret band and excited state absorption due to presence of a long-lived triplet state. Lastly, the spectroscopic results showed that slightly changing the structure of the porphyrins from the meso-units does not change much the interaction with nanocarbon materials.
APPROVED
Keywords: Photoinduced electron transfer; charge transfer; donor-acceptor systems; photophysics; porphyrins; push-pull porphyrins; methylammonium lead triiodide (MAPbI3) perovskite film; graphene carboxylate (GC); fullerene (C60); ultrafast; time-resolved spectroscopy; solar energy conversion